Convergence and divergence of private law in Asia - Towards an Asian Legal Order: Conversations on Convergance (Conference) (2018 : Singapore Management University); Low, Gary (Lawyer) (Cambridge : Cambridge University Press, 2022)
There have been an increasing need for greater integration of many Asian economies, either within the confines of ASEAN or on a more geo-economically strategic scale including major Asian jurisdictions like China, Japan, and Korea. A number of key personalities within the regional legal fraternity have advanced views that such integration ought to occur through the harmonization of legal rules, arguing that in doing so, uncertainty and other transaction costs would be reduced and commercial confidence within the region concomitantly increased. This edited volume brings together eminent and promising scholars and practitioners to investigate what convergence and divergence means in their respective fields and for Asia. Interwoven in the details of each tale of convergence is whether and how convergence ought to take place, and in so choosing, what are the attendant consequences for that choice.
Introduction / Dr Gary Low -- Uniform Law and the production and circulation of legal models / Dr Luca Castellani -- Convergence, divergence and diversity in Financial Law : the experience of the UNCITRAL Model Law on cross-border insolvency / Associate Professor Andrew Godwin -- The New York Convention and the UNCITRAL Model Law on International Commercial Arbitration : existing models for legal convergence in Asia? / Dr Michael Hwang SC -- Convergences and divergences : comparing contractual and organisational models in international regulatory cooperation / Professor Fabrizio Cafaggi -- Law as a market standard : voluntary unification in contract and Company Law / Professor Andreas Engert -- Is harmonisation of Asian Contract Law possible? The example of the European Union / Dr Mateja Durovic & Professor Geraint Howells -- The presumption of regularity in Chinese corporate contracting : evidence and prospect of regional convergence / Dr Charles Zhen Qu -- Mind the gap : studying the implementation discrepancy for the ASEAN economic community / Dr Sanchita Basu Das -- The rule of law as key to the ASEAN legal order : and how is it to be ensured? / Professor Sir Francis Jacobs KCMG QC -- How Asian should Asian Law be? An outsider's view / Professor Ralf Michaels.
Title from publisher's bibliographic system (viewed on 18 Feb 2022).
Keywords: Commercial law -- East Asia -- International unification -- Congresses; Commercial law -- Southeast Asia -- International unification -- Congresses